2022
DOI: 10.1371/journal.pone.0279370
|View full text |Cite
|
Sign up to set email alerts
|

Moringa isothiocyanate-1 inhibits LPS-induced inflammation in mouse myoblasts and skeletal muscle

Abstract: This study aims to investigate the anti-inflammatory effects of moringa isothiocyanate-1 (MIC-1) extracted from seeds of Moringa oleifera Lam. in lipopolysaccharide (LPS)-induced inflammation models. MIC-1 decreased nitric oxide production and reduced the expression of pro-inflammatory markers (TNF-α, Ifn-α, IL-1β, IL-6) in C2C12 myoblasts. The daily oral treatment of MIC-1 (80 mg/kg) for three days significantly reduced the expression of pro-inflammatory markers in gastrocnemius muscle tissue of LPS-treated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Moringine-specific benzyl ITC from Moringa Oleifera modulated the Nrf2/AER pathway, proinflammatory biomarkers, and apoptotic pathway in different mouse and rat models (Galuppo et al, 2014. In another mouse model (LPS induced), it was found that ITCs effectively decreased TNF-α, IL-1β, IL-6 and inhibited NF-kβ (Sailaja et al, 2022). It also downregulated senescence as it promoted neuronal repair in in vitro Aβ induce SH5Y5Y cells (Silvestro et al, 2021).…”
Section: Bioavailability Of Glcs and Itcsmentioning
confidence: 99%
“…Moringine-specific benzyl ITC from Moringa Oleifera modulated the Nrf2/AER pathway, proinflammatory biomarkers, and apoptotic pathway in different mouse and rat models (Galuppo et al, 2014. In another mouse model (LPS induced), it was found that ITCs effectively decreased TNF-α, IL-1β, IL-6 and inhibited NF-kβ (Sailaja et al, 2022). It also downregulated senescence as it promoted neuronal repair in in vitro Aβ induce SH5Y5Y cells (Silvestro et al, 2021).…”
Section: Bioavailability Of Glcs and Itcsmentioning
confidence: 99%
“…Moringine-specific benzyl ITC from Moringa Oleifera modulated the Nrf2/AER pathway, proinflammatory biomarkers, and apoptotic pathway in different mouse and rat models ( Galuppo et al, 2014 , ( Galuppo et al, 2015 ). In another mouse model (LPS induced), it was found that ITCs effectively decreased TNF-α, IL-1β, IL-6 and inhibited NF-kβ ( Sailaja et al, 2022 ). It also downregulated senescence as it promoted neuronal repair in in vitro Aβ induce SH5Y5Y cells ( Silvestro et al, 2021 ).…”
Section: Role In Neuroprotection Ache Inhibition and Neuroinflammator...mentioning
confidence: 99%
“…2 Mouse skeletal myoblasts are cells that rely on anchorage, necessitating the provision of a solid substrate for the creation of cell-based meat. 3 These solid substrates, also known as cell culture scaffolds, play a crucial role in the development of cell-based meat. 4 An optimal scaffold for cell-based meat should be biocompatible, possess a suitable microstructure, offer sufficient mechanical strength, and most importantly, facilitate cell adhesion and sustain metabolic functions.…”
Section: Introductionmentioning
confidence: 99%